Propagation of Mobile Communication with Tree Obstacle used OFDM-QAM at 10 GHz - Andrita Ceriana Eska (JURNAL INFOTEL, 2019)
This research focused about mobile communication systems at line communication of road. Frequency communication was used 10 GHz. The tree was obstacle at every node of line communication. That communication was modeled with single diffraction. Single knife edge was used for that diffraction model. The communication transmission that used was Orthogonal Frequency Division Multiplexing. The modulation variation that used was consisted of 16 QAM and 64 QAM. Analysis that used was consisted of modulation variation, transmitter power variation, and coverage area variation. The result showed that SNR was decreased when transmitter power was increased, the value BER 64 QAM lower than BER 16 QAM, and percentage of coverage area that obtained was around 96%.